FIRST PRINCIPLES STUDY ON ELECTRONIC AND OPTICAL PROPERTIES OF CoX (X=Cr, Mn, Ti, V) co-DOPED ZnO SEMICONDUCTOR - Harry Prayoga; Abdul Rajak; Agustina Widiyani; Priyan Prayogo; Fatimatul Musfiroh; Indra Pardede (Universitas Mataram, 2026)
The development of solar energy materials is essential for achieving the Sustainable Development Goals (SDGs). However, their performance is often limited by the electronic and optical properties of commonly used semiconductors. Unlike previous DFT studies mostly focused on non–transition metal dopants (e.g., Al, Ga), this work explores pristine ZnO, single cobalt (Co) doping, and CoX (X = chromium (Cr), manganese (Mn), titanium (Ti), and vanadium (V)) codoping to reveal how single and dual 3d-orbital interactions modify its electronic and optical behavior. This study investigates the effects of transition metal codoping CoX (X = Cr, Mn, Ti, V) on ZnO using Density Functional Theory (DFT) and DFT with Hubbard U correction (DFT+U) within the Generalized Gradient Approximation (GGA) to evaluate opto-electronic properties. The bandgap of pristine ZnO was calculated as 0.80 eV with standard DFT, while ZnO-Co and ZnO-CoX exhibited zero bandgap with a flatband due to conduction band overlap with the Fermi level, indicating metallic behavior resulting from d-orbital contributions. DFT+U improved the pristine ZnO bandgap to 1.08 eV, although Co-doped and CoX co-doped remained metallic. Orbital resolved analysis shows that Ti and V introduce states near the valence band, while Cr and Mn shift states deeper below the Fermi level, reflecting distinct d-orbital interactions. The theoretical band gaps underestimated experimental values due to strong electron correlation in ZnO. Optical analysis revealed that Co and CoX codoping shifts the absorption edge into the visible range and enhances the absorption intensity. The presence of dopants alters the electronic band structure and enhances optical absorption in the visible range, underscoring their effectiveness in engineering ZnO-based semiconductors for optimized optoelectronic responses.